Comparative Analysis Of Financial Performance In Banking Companies During Covid-19 - Ningsih, Rahmawati Rahayu; Wirananda , Henny Andriyani (Lembaga Riset Ilmiah, 2024)
The purpose of this study is to ascertain and evaluate whether there are any appreciable variations in ROA, ROE, CAR, and NPL at the Indonesian state bank (BNI) and Bank Sumut over the course of COVID-19. Research of this kind is quantitative. Financial statements in the form of balance sheets at the State Bank of Indonesia (BNI) and Bank of North Sumatra for the four years from 2018 to 2021 served as the research instrument utilized to collect data. The annual financial statements of the Bank of North Sumatra and the Indonesian state bank (BNI) served as the study's population. The census method is the sampling approach employed (total sampling). The independent sample t-test was the method of data analysis applied. In contrast to the ROA and NPL variables, which show a significant difference in financial performance between Bank Negara Indonesia (BNI) and Bank Sumut, the results of the analysis using the independent sample t-test on the CAR and ROE variables show no significant difference in financial performance between Bank Negara Indonesia (BNI) and Bank Sumut.